Graphene-based composites for biomedical applications. Issue 3 (3rd July 2022) - Laraba, Selsabil Rokia; Luo, Wei; Rezzoug, Amine; Zahra, Qurat ul ain; Zhang, Shihao; Wu, Bozhen; Chen, Wen; Xiao, Lan; Yang, Yuhao; Wei, Jie; Li, Yulin
ABSTRACT: Over the last decade, the superior properties of graphene have contributed to intensive studies on the fabrication and applications of graphene nanocomposites. Ex-situ homologous recombination and recombination techniques were listed. Because of their remarkable features, including thermal conductivity and high-specific area, graphene and its derivatives have a significant prospective for medical and biological applications, including drug delivery and bio-imaging. The usage of graphene-based nanomaterials is a hot topic in medicinal research. Many research studies have been performed on graphene-based composites, but only a few reviews have been published regarding their applications in the biomedical field and potential risk factors associated with human well-being and the environment. Hence, this review paper aims to provide in-depth information on ongoing knowledge and results about the properties of graphene-based composites. The discovery, developmental methods, structural properties, and synthesis of graphene nanomaterials have been discussed. After a brief description of the most common methods used for fabricating or extracting graphene derivatives, the main steps of graphene-based composite preparation are introduced. Applications of graphene-based composites in drug delivery, medical, and biomedical fields have been addressed. Finally, the future perspectives and challenges associated with the applications of graphene-based composites have been summarized. GRAPHICAL ABSTRACT: UF0001